Post-inflationary production of particle dark matter: Non-minimal natural and Coleman–Weinberg inflationary scenarios - Anish Ghoshal; Maxim Yu. Khlopov; Zygmunt Lalak; Shiladitya Porey (Physics Letters B)
We investigate the production of non-thermal fermionic dark matter particles during the reheating era following slow roll inflation, driven by inflaton φ non-minimally coupled to the curvature scalar, R. Two types of non-minimal couplings are considered: ξφ2R for both natural (referred to as NM-N) and for Coleman-Weinberg (referred to as NM-CW) inflation, and α(1+cos⁡(φfa)) only for natural inflation (referred to as NMP-N), where α and ξ are dimensionless parameters and fa is an energy scale. We determine benchmark values for slow roll inflationary scenarios satisfying current bounds from Cosmic Microwave Background (CMB) radiation measurement and find the mass of inflaton to be Image 1 for all three inflationary scenarios and tensor-to-scalar ratio, r∼0.0177 (for NM-N), ∼0.0097 (for NMP-N), and r∼0.0157 (for NM-CW) which fall inside 1−σ contour on scalar spectral index versus r plane of Planck2018+Bicep3+Keck Array2018 joint analysis, and can be probed by future CMB observations e.g. Simons Observatory. We then show that dark matter particles produced from the decay of inflaton can fully match the present-day cold dark matter (CDM) yield, as well as other cosmological constraints, if the coupling value between inflaton and dark matter, yχ, and the dark matter mass, mχ, are within the range 10−1≳yχ≳10−20 for NM-N and NMP-N (10−4≳yχ≳10−20 for NM-CW) and Image 2 (for NM-N, NMP-N, and NM-CW). The exact range of yχ and mχ varies with different benchmark values as well as parameters of inflation, like energy scale of inflation and r, some of which are within reach of next-generation CMB experiments.